Cinzas volantes: uma alternativa para compósitos reforçados com partículas - FERREIRA, Victor Hugo Mafra Monfredo (2021)
As industrial growth evolves, it has brought with it the generation of waste, which is a potential environmental problem. The study of the properties of these materials, as well as the development of techniques aimed at their possible reuse, is fundamental for environmental preservation. Thus, in this work, polymeric matrix composites were made using the fly ash industrial residue, with granulometries of 100, 200, 325, and 400 mesh. The manufacturing was performed through the manual manufacturing method hand lay up, with proportions varying between 0 %, 10 %, 20 % and 30 % in mass of waste. Isophthalic polyester resin was used as the matrix phase, with cobalt accelerator in the ratio of 1.5% v / v and initiator in the proportion of 1% v / v. Mineralogical analysis of the residue was performed using the X-Ray Diffraction technique (XRD), the morphology and chemical charaterization was performed by Scanning Electron Micoscope (SEM) and Energy Dispersive Spectroscopy (EDXS). After making the composite materials and preparing the specimens, physical tests were carried out following the norms and guidelines established by ASTM D 792, ASTM D 2734 e ASTM D 570 and the mechanical tests of flexion and traction, according to ASTM 790 and ASTM 3039, respectively, with the analysis of the fracture surface performed with the aid of a Scanning Electron Microscope. The flame propagation rate was obtained through the horizontal flammability test, following the ASTM D 635 standards. The mineralogical, morphological and chemical characterizations of the fly ash waste were consistente with the literature. It was found that the physical properties of the composites (water absorption, apparent porosity and bulk density) increased with the gradual insertion of ash in the matrix for all particle sizes. Through the mechanical tests, an increase in resistance was noted for both flexure and tensile tests compared to the matrix, configuring the residue as a reinforcement load, with the exception of the 30% composition with 325 mesh grain size for flexure. Through SEM analysis, it was possible to observe a good dispersion of residue in the matrix for the proportions of 30 % (100 and 200 mesh), as well as the presence of defects. All the tested materials exhibited excellent flame resistance properties, when compared to the guidelines of the standard used for the flammability test, with emphasis for the composition of 30 % with a 400 mesh grain size.